Analysis Of The Value Of Time And Patience In Surah Al-'Asr As The Basis For Developing Teachers' Pedagogic Competencies In Fostering Students' Adaptability Character In The Era Of Digital Change - Fadllurrahman, Fadllurrahman; Arizqi Ihsan Pratama; Pahri Siregar; Nahriyah Harahap (Institut Muslim Cendekia, 2025)
This study aims to analyze the role of the value of time and patience in Surah Al-'Asr as the basis for developing teachers' pedagogical competence in shaping students' adaptability character in the digital era. The research method used is a qualitative study with document analysis of various literature sources, including classical and contemporary tafsir as well as current research on character education and modern pedagogy. Data analysis techniques were carried out through identification, reduction, and interpretation of documents to find the relevance of the value of time and patience to teachers' pedagogical competence. The results show that the value of time helps students develop discipline, planning, and efficiency in learning, while the value of patience builds mental and emotional resilience in facing academic and social challenges. Teachers with good pedagogical competence are able to integrate these two values in learning methods, such as through time management-based assignments and challenge-based learning that instills perseverance.